George iv´s curiosity: - Rodrigo Jungmann de Castro (Kalagatos, 2021)
In this paper I pose a problem for Russell’s analysis in “On Denoting” of the propositions expressed by attitude ascription sentences in which whether-clauses are embedded. My contention is that Russell’s analysis faces a difficulty overlooked by him. My argument proceeds as follows. I note that Russell’s proposed rendering does capture, by intuitive standards, what we normally mean by an utterance of a sentence differing from the one in Russell’s examples in a slight but very significant way, namely by having the adjective ‘only’ inserted after the definite article. Since the propositions expressed by the sentence in Russell’s example and by the variant I offer may differ in truth-value, it follows that the Russellian treatment of such clauses may be incorrect.